Depletion of cardiolipin induces major changes in energy metabolism in Trypanosoma brucei bloodstream forms - Serricchio, Mauro; Hierro-Yap, Carolina; Schädeli, David; Ben Hamidane, Hisham; Hemphill, Andrew; Graumann, Johannes; Zíková, Alena; Bütikofer, Peter (FASEB journal, 2021)
The mitochondrial inner membrane glycerophospholipid cardiolipin (CL) associates with mitochondrial proteins to regulate their activities and facilitate protein complex and supercomplex formation. Loss of CL leads to destabilized respiratory complexes and mitochondrial dysfunction. The role of CL in an organism lacking a conventional electron transport chain (ETC) has not been elucidated. Trypanosoma brucei bloodstream forms use an unconventional ETC composed of glycerol-3-phosphate dehydrogenase and alternative oxidase (AOX), while the mitochondrial membrane potential (ΔΨm) is generated by the hydrolytic action of the Fo F1 -ATP synthase (aka Fo F1 -ATPase). We now report that the inducible depletion of cardiolipin synthase (TbCls) is essential for survival of T brucei bloodstream forms. Loss of CL caused a rapid drop in ATP levels and a decline in the ΔΨm. Unbiased proteomic analyses revealed a reduction in the levels of many mitochondrial proteins, most notably of Fo F1 -ATPase subunits and AOX, resulting in a strong decline of glycerol-3-phosphate-stimulated oxygen consumption. The changes in cellular respiration preceded the observed decrease in Fo F1 -ATPase stability, suggesting that the AOX-mediated ETC is the first pathway responding to the decline in CL. Select proteins and pathways involved in glucose and amino acid metabolism were upregulated to counteract the CL depletion-induced drop in cellular ATP.
Keywords: energetický metabolismus; Mitochondria; adenosintrifosfát; elektronový transportní řetězec; Cardiolipins; Glycerolphosphate Dehydrogenase; Oxidoreductases; proteom; membránové proteiny; Membrane Proteins; mitochondriální membrány; protozoální proteiny; kardiolipiny; Electron Transport Chain Complex Proteins; Organisms, Genetically Modified; genový knockout; oxidoreduktasy; Plant Proteins; mitochondriální proteiny; Trypanosoma brucei brucei; Transferases (Other Substituted Phosphate Groups); proteomika; Mitochondrial Proteins; spotřeba kyslíku; Oxygen Consumption; Gene Knockout Techniques; transferasy pro jiné substituované fosfátové skupiny; glycerolfosfátdehydrogenasa; Energy Metabolism; geneticky modifikované organismy; Adenosine Triphosphate; membránový potenciál mitochondrií; Protozoan Proteins; Proteomics; Mitochondrial Membranes; Proteome; Membrane Potential, Mitochondrial; mitochondrie; rostlinné proteiny